Evaluation of Organ Doses to Female Reproductive System During Abdominal CT Imaging: A Phantom Study - Kayaokay, Duygu Tuncman; Yalcin, Berrin; Ata, Aysun Ozsoy; Saglam, Ozge Coskun; Gunay, Osman; Demir, Mustafa; Kesmezacar, Fahrettin Fatih (GALENOS PUBL HOUSE, 2026)
Introduction: This study aimed to determine the absorbed radiation doses in radiosensitive female pelvic organs during abdominal computed tomography (CT) imaging using thermoluminescent dosimeters (TLD-100) and an anthropomorphic phantom. Methods: A Computerized Imaging Reference Systems, Inc. female pelvic anthropomorphic phantom was used to simulate realistic human anatomy. TLD-100 dosimeters were positioned within organ-equivalent cavities corresponding to the ovaries, uterus, and urinary bladder. CT scans were performed using a Toshiba Aquilion 64-slice scanner with standard abdominal parameters (120 kVp, 300 mA, 5 mm slice thickness, pitch 1.0). After exposure, TLDs were read using a Harshaw 3500 reader, and organ doses were calculated based on calibration coefficients. Results: The urinary bladder exhibited the highest mean absorbed dose (27.89 mGy), followed by the fundus uteri (26.34 mGy), left ovary (23.22 mGy), cervix uteri (21.88 mGy), and right ovary (20.91 mGy). Lower doses were measured in deeper or more peripheral regions, such as the recessus rectouterina (19.37 mGy) and the medulla spinalis (16.73 mGy). Conclusion: The results indicate that even under standard clinical protocols, radiosensitive organs of the female reproductive system receive measurable radiation doses during abdominal CT. These findings emphasize the need for protocol optimization and shielding strategies to minimize exposure, especially in reproductive-age women.
Keywords: Experimental dosimetry; phantom study; female reproductive system; TLD; General & Internal Medicine